Aphanius irregularis, a new killifish from south-western Anatolia (Cyprinodontiformes: Aphaniidae) - Yoğurtçuoğlu, Baran; Freyhof, Jörg (Zootaxa, 2018)
Aphanius irregularis, new species, is described from the spring Kaklık in the Büyük Menderes River drainage in south-western Anatolia. Males of A. irregularis are distinguished from males of other species of the A. anatoliae group by having irregularly set and shaped dark-brown flank-bars often fused to each other, forming rows of vertically elongated silvery blotches and many small silvery spots or fields of small vermiculation, disconnected from silvery bar interspaces on flank. Males of A. irregularis are distinguished from males of some other species of the A. anatoliae group by having a wide, dusty grey or black anal-fin margin, often interrupted in small individuals; a narrow, white stripe or a series of white spots on the black dorsal-fin base; and often some white blotches in the middle of the dorsal fin. Females of A. irregularis are distinguished by having a vermiculate brown colour pattern, usually with a mid-lateral series of short stripes. The available molecular genetic data suggest that A. irregularis is closely related to A. maeandricus, which occurs in other springs in the Büyük Menderes River drainage. Geological data suggest that both spring complexes have not been connected until they were caught by the Büyük Menderes River in the Late Quaternary, no more than 0.8 million years ago.